3 William Waller Hening, The Statutes at Large: Being a Collection of all the Laws of Virginia 335-38 (1823) - (:unkn) unknown (My University, 1705)
The militia included "all male persons whatsoever, from sixteen to sixty years of age . . . to serve in horse or foot." An infantryman needed "a firelock, muskett or fusee well fixed, a good sword," cartridge box, and ammunition. He had to bring six rounds of ammunition to muster. Additionally, he had to "have at his place of abode two pounds of powder and eight pounds of shott, and bring the same into the field with him when thereunto specially required." A horseman needed the usual tack and ammunition accoutrements along with a pair of pistols and a sword. He had to bring eight rounds of ammunition to muster. At his usual place of abode, he also had to keep a well fixed carabine, two pounds of powder and eight pounds of shot. The act made it unlawful for creditors to seize a militiaman's arms as payment for debts. If a creditor nevertheless took someone's militia equipment, the seizure would "be unlawful and void." Any "officer or person that presumes to make or serve the same" (e.g., a sheriff serving a writ of attachment) would "be lyable to the suit of the party grieved, wherein double damages shall be given upon recovery."
Keywords: MILITIAS; REQUIRED POSSESSION